Nekrolog over Kaj Thaning - Pedersen, Kim Arne (Grundtvig-studier, 1994)
Kaj Thaning 4.6. 1904 - 6.6. 1994 By Kim Arne Pedersen.A few days after his ninetieth birthday, Kaj Thaning died peacefully in his home in Båring, where he had been a clergyman for a generation, and where his monumental work, the thesis .Man First.... was made ready for publication in 1963. Kaj Thaning was bom into a family with roots in influential circles of Grundtvigianism, but as a young undergraduate he came into contact with the Danish Tidehverv movement which introduced the dialectic theology in Denmark. Together with a number of other young theologians Kaj Thaning was connected with both Tidehverv and Grundtvigian circles, and the group was consequently termed .Tidehverv Grundtvigianism.. Thaning became the Grundtvig interpreter within this group, and published his interpretations in a number of books and articles, and a precis of the main thoughts in his thesis was translated into a number of foreign languages in connection with Grundtvig’s anniversary in 1972. Thaning was a vicar through the greater part of his life, but was also deeply engaged in numerous other activities: establishing a folk high school, participating in debates on topical issues, and, in co-operation with the pioneers of the Grundtvig Society, working out the register of Grundtvig’s unprinted manuscripts, a work amply demonstrating his impressive abilities as a research historian. Thaning was a member of the Grundtvig Society Committee from 1948. As early as 1949 he wrote his first major article in Grundtvig Studies, and until recent years he contributed a large number of long or short papers to the yearbook, always impressive in their profundity and perspicacity. As an interpreter of Grundtvig, Thaning has reached far beyond the academic circles to which scientific research is usually restricted. Thaning’s thesis - that the modem relevance of Grundtvig’s writings is closely bound up with his struggle with his personal mixture of the human and the Christian - has had a decisive influence on the Danish cultural and theological debate in the years after World War II, in that it matches with Denmark’s development from an agricultural to an industrial and urban society, and with the decreasing influence of the religious revival movements. Thaning’s secular-theological emphasis on the separation of the human and the Christian as the essential theme in Grundtvig’s writings legitimized this development, but at the same time Thaning’s thesis bore evidence of a profound personal struggle and of a theologically thoroughly contemplated interpretation of Grundtvig, encompassing his entire work. All the same, it seems fair today to view Thaning’s thesis in the light of the theological currents he met on his way, a theological-historical view which may be understood in continuation of the criticism of Thaning’s thesis, raised by recent Grundtvig research, seeking its arguments in incarnation theology. In recent years, this criticism has paved the way for a renewed occupation with Grundtvig’s liturgical theology, and has been able to fertilize Grundtvig’s thoughts in an international, ecumenical-theological context. Thaning, however, was unaffected by this criticism; he remained forever prepared to raise objections to his critics. Thus, from recent years, the present writer remembers Thaning’s unremitting and unyielding defence of his thesis, but also his kindness and helpfulness in connection with the present writer’s first attempts in Grundtvig research.The fact that Thaning’s position has been abandoned in modem research does not weaken the greatness of his work. Thaning’s critics, too, have been - if adversely - influenced by his thesis, whose definition of the relationship between the human and the Christian has left an indelible trace in Danish theology.